Pertanggungjawaban Tindak Pidana Pembunuhan : Studi Perbandingan Hukum Pidana Indonesia Dengan Arab Saudi - Fladyo Pratama; Daffa Putra Rasmawan (Universitas Sains dan Teknologi Komputer, 2025)
Abstract. Murder is the most serious criminal offence against human life which is universally regulated in various criminal law systems. Although however, the approach to the form and mechanism of criminal responsibility for murder offenders for perpetrators of murder can vary significantly between countries, influenced by legal philosophy,legal system adopted, and socio-cultural background. This research is a This research is a normative research, using comparative approach and Statute Approach This research examines This research examines relevant laws and regulations, such as the Criminal Code (hereinafter referred to as KUH PIDANA). This approach is used to compare the accountability of the Indonesian This approach is used to compare the accountability for the offence of murder in Indonesia with Saudi Arabian law to understand the differences and to find solutions. differences as well as to find solutions or recommendations for legal issues of the best sanctions for perpetrators of murder in Indonesia. murder in Indonesia. This research focuses on the criminal evidence system evidence system and the comparison of death penalty sanctions between Indonesia and Saudi Arabia. Arabia. The analysis uses inductive method. The results of Saudi Arabian criminal research is more restorative than Indonesian criminal law as evidenced by the victim's family choosing the punishment for the perpetrator.